Experimental Study on Effect of Changing Welding Current on Mechanical and Metallurgical Properties of Seam Welding Joint for Low Carbon Steel AISI 1005 (0.8 mm) (University of Thi-Qar Journal for Engineering Sciences, 2013)
The aim of this work is to study the effect of changing welding current on the mechanical and metallurgical properties and choose the best welding current depend on result of study. The present work is an experimental study on effect of changing welding current on properties of seam welding joint for low carbon steel AISI 1005. Experiments results shows with increase welding current, hardness number will increase, also differentness in hardness number between weld nugget and HAZ (Heat Affected Zone) will increase and border of HAZ become bigger. Best mechanical results was achieved when welding current increased this doesn't mean that the highest current will become the suitable one, because the higher current will cause burin through in metal sheets and will cause leakage in products (liquid or gas storage tank), also will effect on grain size and microstructure due to changes in cooling rate, also the final shape of joints its important because most application of this type of weld is weight-goods industries (for civil using), so when use high welding current the final shape of joint will deform. Depended on above the best welding current rang is between 17 ? I < 19 K Amp.